Risk and protective factors associated with adolescent girls' substance use: Data from a nationwide Facebook sample. Issue 4 (1st October 2016) - Schwinn, Traci M.; Schinke, Steven P.; Hopkins, Jessica; Thom, Bridgette
ABSTRACT: Background : Despite overall reductions in teenage substance use, adolescent girls' rates of substance use remain unacceptably high. This article examines whether girls' substance use is associated with general risk and protective factors (goal setting, problem solving, refusal skills, peer use, and self-efficacy) and gender-specific risk and protective factors (communication style, coping skills, self-esteem, body image, perceived stress, anxiety, and depression). Methods : Cross-sectional data were collected in 2013 via online surveys from a nationwide sample of adolescent girls ( N = 788), aged 13 and 14 years, who were recruited through Facebook. Results : In multivariate analyses, controlling for correlates of adolescent substance use, 11 of the 13 general and gender-specific risk and protective factors were consistently associated with past-month alcohol, cigarette, and other drug use in the expected direction; past-month marijuana use was associated with 8 of the 13 factors. Refusal skills, peer use, coping, and depressive mood were most consistently and strongly associated with substance use. Conclusions : Substance abuse prevention programs targeting adolescent girls should focus on such general risk and protective factors as problem solving, refusal skills, peer influences, and self-efficacy, as well as such gender-specific risk and protective factors as communication style, coping, self-esteem, body image, perceived stress, and mood management.